Meeting in the middle: Hybrid clay three-dimensional fabrication processes for bio-reef structures. (June 2019) - Trilsbeck, Matthew; Gardner, Nicole; Fabbri, Alessandra; Haeusler, Matthias Hank; Zavoleas, Yannis; Page, Mitchell
Despite the relative accessibility of clay, its low cost and reputation as a robust and sustainable building material, clay three-dimensional printing remains an under-utilized digital fabrication technique in the production of architectural artefacts. Given this, numerous research projects have sought to extend the viability of clay three-dimensional digital fabrication by streamlining and automating workflows through computational methods and robotic technologies in ways that afford agency to the digital and machinic processes over human bodily skill. Three-dimensional printed clay has also gained prominence as a resilient material well suited to the design and fabrication of artificial reef and habitat-enhancing seawall structures for coastal marine environments depleted and disrupted by human activity, climate change and pollution. Still, these projects face similar challenges when three-dimensional printing complex forms from the highly plastic and somewhat unpredictable feed material of clay. In response, this article outlines a research project that seeks to improve the translation of complex geometries into physical clay artefacts through additive three-dimensional printing processes by drawing on the notion of digital craft and giving focus to human–machine interaction as a collaborative practice. Through the case study of the 1:1 scale fabrication of a computationally generated bio-reef structure using clay as a feed material and a readily available Delta Potterbot XLS-2 ceramic printer, the research project documents how, by exploiting the human ability to intuitively handle clay and adapt, and the machine's ability to work efficiently and with precision, humans and machines can fabricate together . With the urgent need to develop more sustainable building practices and materials, this research contributes valuable knowledge of hybrid fabrication processes towards extending the accessibility and viability of clay three-dimensional printing as a resilient material and fabrication system.